Pembinaan Spiritualitas ALMA Puteri dan Pendampingan Bagi Pengasuh Untuk Pelayanan Kepada Anak-Anak Berkebutuhan Khusus Di Bhakti Luhur Malang - Kii, Rosalia Ina; Hatmoko, Tomas Lastari (SAPA - Jurnal Kateketik dan Pastoral, 2025)
Modern life brings significant implications for human morality, spirituality, and identity, including within the context of serving children with special needs. At the Bhakti Luhur Foundation, spiritual formation plays an essential role in helping caregivers recognize that their service is an act of devotion to Jesus, who is present in the poor and suffering children they accompany. However, various challenges arise, such as incidents of violence, low commitment, and ineffective use of time due to distractions from social media. This study aims to evaluate the effectiveness of the ALMA Puteri spiritual formation and caregiver accompaniment in carrying out this service. Using a descriptive qualitative method through interviews, observations, and documentation, the study found that spiritual formation has been provided from the beginning, yet its impact is not fully optimal. Service becomes more meaningful when caregivers understand that their work is directed toward Christ and is lived out in community life through shared meals, communal prayer, and regular conversations. The main obstacle lies in caregivers’ initial motivation, which is often oriented toward obtaining education and certificates. Therefore, more intensive and consistent spiritual formation is needed to enhance caregiving quality and deepen commitment to service.